2015
DOI: 10.1016/j.optmat.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Nd doped (Lu, Gd)3(Ga, Al)5O12 single crystal by the micro pulling down method and their scintillation properties

Abstract: a b s t r a c tNd 1 mol% doped (Lu, Gd) 3 (Ga, Al) 5 O 12 (LGGAG) single crystals were grown by the micro-pulling down (l-PD) method. Luminescence and scintillation properties such as absorption, excitation and emission spectra, light yield and decay time were evaluated. Nd1%:Lu 3 Al 5 O 12 showed the highest light output of around 8200 photons/MeV among the grown crystals. Scintillation decay time of Nd:Y 3 Al 5 O 12 was 1.32 ls (36%) 2.02 ls (64%). Nd:Lu 3 Ga 3 Al 2 O 12 was relatively high dense scintillato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In radioluminescence process, when the energy absorbed in the host material is induced by high-energy radiation, then the energy passes to the RE emission center and the photons are emitted in a relaxation process. The radioluminescent or scintillator materials are used such as in the high energy or nuclear physics detectors, the advanced techniques for homeland security, the high-tech industrial applications, and the medical imaging techniques (to detect accelerated particles and highenergy photons) (30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…In radioluminescence process, when the energy absorbed in the host material is induced by high-energy radiation, then the energy passes to the RE emission center and the photons are emitted in a relaxation process. The radioluminescent or scintillator materials are used such as in the high energy or nuclear physics detectors, the advanced techniques for homeland security, the high-tech industrial applications, and the medical imaging techniques (to detect accelerated particles and highenergy photons) (30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Nd doped materials are well‐known as solid‐state phosphors because of its near infrared (NIR) characteristics. As scintillation material, different studies have been reported with the scintillation properties of Nd doped oxides . Nd doped NIR phosphors have been regarded to great interest as a new generation NIR emitting scintillator .…”
Section: Introductionmentioning
confidence: 99%
“…As scintillation material, different studies have been reported with the scintillation properties of Nd doped oxides. [4][5][6] Nd doped NIR phosphors have been regarded to great interest as a new generation NIR emitting scintillator. 7 NIR emission of Nd ion due to the 4f-4f transitions has great transparency to the biological tissue, so it has a considerable potential for bio-imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…At present, both Gd 3 Al 2 Ga 3 O 12 :Ce (GAGG:Ce) single crystals and ceramics have been studied by several groups. GAGG:Ce single crystals have been mainly grown by the Czochralski(CZ) method [6][7][8] , micro-pulling down(μ-PD) method [9][10][11] , and Floating Zone(FZ) method [12][13] . GAGG crystals grown by micro-pulling-down (μ-PD) process have a light yield of 56,000 photon/MeV when Ga content locates at 2.7 atoms per garnet formula unit and energy resolution of 5.3% [11] .…”
mentioning
confidence: 99%